2003
DOI: 10.1046/j.1365-3059.2003.00822.x
|View full text |Cite
|
Sign up to set email alerts
|

PCR‐based specific and sensitive detection ofPectobacterium carotovorumssp.carotovorumby primers generated from a URP‐PCR fingerprinting‐derived polymorphic band

Abstract: A 24-mer primer pair was generated by sequencing a URP-PCR fingerprinting-derived polymorphic band that is uniquely shared in Pectobacterium carotovorum ssp . carotovorum strains (Pcc). The primer set (EXPCCF/EXPCCR) amplified a single band of expected size (0·55 kb) from genomic DNA obtained from 29 Pcc strains and three Pectobacterium carotovorum ssp. wasabiae (Pcw) strains, but not from other P. carotovorum subspecies atrosepticum , betavasculorum or odoriferum , or from other Erwinia spp. or bacterial gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 30 publications
3
63
0
3
Order By: Relevance
“…Detection of bacteria with primers EXPCCF and EXPCCR, specific for P. carotovororum subsp carotovorom, P. carotovorum sub sp carotovorum was amplified with a set of primers EXPCCF and EXPCCR as described by [12], synthesized by Bioneer (England). Amplification was performed in a final volume of 50 µL PCR mixture containing 5 µL 10X PCR buffer, 0.5 µL each of desoxy nucleotides dATP, dCTP, dGTP, dTTP, 0.5 µmol (2.5 U)Taq polymerase and 1 µL (100 ng) primers.…”
Section: Detection Of Bacteria With Published Specific Primersmentioning
confidence: 99%
See 2 more Smart Citations
“…Detection of bacteria with primers EXPCCF and EXPCCR, specific for P. carotovororum subsp carotovorom, P. carotovorum sub sp carotovorum was amplified with a set of primers EXPCCF and EXPCCR as described by [12], synthesized by Bioneer (England). Amplification was performed in a final volume of 50 µL PCR mixture containing 5 µL 10X PCR buffer, 0.5 µL each of desoxy nucleotides dATP, dCTP, dGTP, dTTP, 0.5 µmol (2.5 U)Taq polymerase and 1 µL (100 ng) primers.…”
Section: Detection Of Bacteria With Published Specific Primersmentioning
confidence: 99%
“…Amplification was performed in a final volume of 50 µL PCR mixture containing 5 µL 10X PCR buffer, 0.5 µL each of desoxy nucleotides dATP, dCTP, dGTP, dTTP, 0.5 µmol (2.5 U)Taq polymerase and 1 µL (100 ng) primers. PCR amplification was performed in an Eppendorf thermal cycler (Germany), using the following program [12] one cycle of 4 min at 94°C as initial denaturation step, 30 cycles of 1 min at 94°C, 1 min at 60°C, 2 min at 72°C and one cycle as final extension for 7 min at 72°C.…”
Section: Detection Of Bacteria With Published Specific Primersmentioning
confidence: 99%
See 1 more Smart Citation
“…to cause blackleg is undisputed (Lumb et al 1986;Helias et al 2000;Toth et al 2003) but the role of Pcc in the blackleg syndrome is controversial. Pcc is widely distributed in the world and has a broad host range (De Boer et al 1987;Smith and Bartz 1990;Kang et al 2003). Studies under high temperature conditions in North America Harrison 1977, 1980) and Australia (Peltzer and Sivasithamparam 1985) showed that Pcc isolates, inoculated into tubers or stems, could cause typical blackleg symptoms in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Within the past 30 years, there has been a shift from microbiological and serological methods to molecular approaches (PalacioBielsa et al, 2009;Czajkowiski et al, 2014). DNA markers have been used for the rapid detection of different strains of P. carotovorum subspecies carotovorum (Pcc) (Kang et al, 2003;Zhu et al, 2010;Rahmanifer et al, 2012;Azadmanesh et al, 2013). DNA sequence analysis of gene pmrA, which is linked to pathogenicity (response regulator), was used to evaluate the relationship among Pcc isolates collected from different regions of Morocco and results were equivalent to enterobacterial repetitive intergenic consensuspolymerase chain reaction (ERIC-PCR) and 16S rDNA sequencing (Kettani-Halabi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%